2018
DOI: 10.18805/ijar.b-3607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of feeding value of rice based Distillers Dried Grains with Solubles (DDGS) for broiler chickens

Abstract: A biological experiment of 160 day old chicks for six weeks was undertaken with completely randomized design (CRD) divided into five treatments, each consisting of 4 replicates and 8 chicks in each replicate. Five experimental diets as per ICAR (2013) were prepared by incorporating rice distillers dried grains with solubles (rDDGS) at inclusion level of (0, 7.5, 10.0, 12.5 and 15.0%). Chemical analysis revealed that rice DDGS on as such basis is high in both crude protein 44.68% and gross energy 4232 kcal/kg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…Thus, both the types of r-DDGS didn't show any negative effect on body weight at the higher level indicating that r-DDGS in the diet was safe for Vanaraja chicks when added to diet up to 10% on the iso-nutrient basis. The results obtained in the current study with dual-purpose rural type chickens corroborate well with the trends reported on broiler chicken by Dinani et al (2019), where r-DDGS was observed to be safe for broiler chicken up to 12.5% and at a further higher level of 15%, significant depression in growth was recorded. However, when r-DDGS was used at 12.5% level in combination with rice gluten meal (15%), adverse effects were reported on the intestinal histomorphometry and microbiology in broiler chicken (Dinani et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Thus, both the types of r-DDGS didn't show any negative effect on body weight at the higher level indicating that r-DDGS in the diet was safe for Vanaraja chicks when added to diet up to 10% on the iso-nutrient basis. The results obtained in the current study with dual-purpose rural type chickens corroborate well with the trends reported on broiler chicken by Dinani et al (2019), where r-DDGS was observed to be safe for broiler chicken up to 12.5% and at a further higher level of 15%, significant depression in growth was recorded. However, when r-DDGS was used at 12.5% level in combination with rice gluten meal (15%), adverse effects were reported on the intestinal histomorphometry and microbiology in broiler chicken (Dinani et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…Weekly protein efficiency ratio differed insignificantly (P>0.05) for all the age group except for 1 st week and maximum protein efficiency ratio was found in T 3 (4.35) followed by T 2 (3.74), T 1 (3.70) and T 0 (3.66) dietary groups during the same age group. The present results are in agreement with the findings of Singh et al (2020) whereas, Dinani et al (2019) reported non-supporting findings to the present results regarding PER in poultry.…”
Section: Resultssupporting
confidence: 88%
“…The increase in feed intake may be due to very high level of non-starch polysaccharides (NSP) in DDGS, which were not digested by the endogenous enzymes of birds, so, birds consumed more feed to overcome the dilution effect of the NSP in order to satisfy their energy and nutrient needs (Barekatain et al 2013). However, corroborated reports for the same trait have been given by Borah et al (2020) and Dinani et al (2019) who stated that DDGS inclusion level in diet decrease feed intake in the broilers.…”
Section: Resultssupporting
confidence: 88%
“…There were twelve different treatments with 4 replicates for each treatment. Two levels of rice DDGS were taken, the best inclusion level from earlier experiments as first level (12.5%) and then adding over and above the best level of 2.5% DDGS to this level (Dinani et al 2019). Protease, xylanase and multienzymes supplementation under different treatments were used to find out the most suitable enzyme for rice DDGS diets.…”
Section: Augmenting Feeding Value Of Rice Distillers Dried Grain With...mentioning
confidence: 99%